Improvement of Rice Flour, Rice Dough and Rice Bread by Transglutaminase - Shuai ZHANG; Xiaoxue GUO; Jing FAN; Xin BIAN; Yang YANG; Chunmin MA; Xiaofei LIU; Yan WANG; Na ZHANG (Shipin gongye ke-ji, 2023)
In order to improve the quality of rice bread and reveal the effects of transglutaminase (TGase) on the quality of rice flour, rice dough and rice bread, and reveal the relationship among the indexes. The silty properties and pasting properties of TGase containing different mass fractions in rice flour, the water distribution, rheological properties and fermentation capability of rice dough, and the specific volume, gas cells and texture of bread were tested. The results showed that 0.60% TGase could improve the silty and pasting properties of rice flour, and increase the stabilization time of rice flour to 8.00±0.77 min. The peak viscosity (PV), valley viscosity (VV) and final viscosity (FV) were increased to 5801.00±30.41, 3805.67±76.14 and 5836.33±106.17 cP, respectively. Breakdown (BD) and setback (SB) of rice flour were reduced to 1990.00±128.11 and 1991.67±34.08 cP. At the same time, TGase increased the tightness of water binding, improved the rheological properties and fermentation capability of rice dough, increased S21 to 9.24%±13.07%, decreased T21 and T22 to 1.40±1.80 and 30.45±2.28 ms, and increased Hm to 8.60±0.11 mm. The porosity was increased to 50.51%±0.90%, which reduced the hardness, adhesiveness and chewiness of rice bread, improved the springiness of rice bread and improved the textural properties of rice bread. Correlation analysis showed that T23 was negatively correlated with the formation time, and Hm was positively correlated with C3, C3~C2 and VV. And BD and SB were negatively correlated, chewiness was positively correlated with C1, specific volume was positively correlated with FV and PV were positively correlated. The results showed that TGase improved the quality of rice flour, rice dough and rice bread, and there were different degrees of correlation among the improved indexes.